Analisis Perubahan Lahan Kawasan Laguna Segara Anakan Selama Periode Waktu (1978 – 2016) Menggunakan Satelit Landsat Multitemporal - Rose Dewi; Muhammad Zainuri; Sutrisno Anggoro; Tjahjo Winanto (Journal Omni-Akuatika, 2016)
Segara Anakan Lagoon (SAL) has the unique characteristics of the region with the high of natural resources biodiversity. The region of SAL is influences by natural factor (estuarine freshwater stream of Citanduy watershed and the high of sedimentation rate) and the variety of anthropogenic factor. The factors lead to the changes in land, because it triggers the decrease of the lagoon water bodies. The aim of the research is to know the changes of the region land use in SAL and its impact. Temporally spatial approach is required to evauate the influence of both factors. Spatial approach is done by using remote sensing method with Geographic Information System, with Multi-Temporal Landsat imagery data processing (the year of 1978, 1994, 2001, 2009, 2011 and 2016). It uses land classification technique (Supervised Classification). It is processed with ER Mapper 7.0 software and displayed with Arc GIS (Jpeg). The analysis result shows that there is 2.703,7 ha extensive shrinkage lagoon in 38 year (1978 - 2016) or there is 71.15 ha per year in land area increase in the last 38 years. It is supported with 4.741,36 ha residential land and 17.962,64 ha field land that cause the degredation of SAL region. The increase of SAL citizenary amount triggers the land conversion for the interest of the various anthropogenic activities. It is supported by the threat of natural factors of high sedimentation level that cause higher SAL pressure. In conclusion, it is needed evaluation and management strategies to overcome the changes of SAL land area by the local government and related parties.